Realizing the Significance of High-Skill Orientation So As to Win In a Global Market: the Mediating Role of Training In International: Exploring the Impact of High-Skill Orientation on International Marketing Strategy (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This study examines the pivot role ofambidextrous skill orientation in the strategy-performance thesis ofInternational firms. Building on the resource based view of the firm,empirically the relationships among competitive strategy, innovation,positional advantage has been examined. Moreover it is necessary to observe theskills needed to be effective in International Marketing, the level ofimportance of each of these skills are present in employees of Internationalfirms, describe the gap between the skills these employees have and the skillsthey need. The study findings have important implications for research onInternational Marketing, high-skill orientation, new venture decision making.